Stabilization and Reactivity of the Lewis Acidic Solvated Phenylcalcium Cation1. Issue 12 (12th February 2013) - Langer, Jens; Köhler, Mathias; Hildebrand, Jörg; Fischer, Reinald; Görls, Helmar; Westerhausen, Matthias
<x xml:space="preserve">Abstract</x> Grignard deluxe: The 1, 2‐dimethoxyethane adduct of phenylcalcium iodide forms the unique solvent‐separated species [(dme)3CaPh]+I− with a highly Lewis acidic metal center. Degradation of DME occurs, yielding calcium methoxide cages, such as [{(dme)Ca}4(CaI)2(μ3‐OMe)8(μ6‐O)], and methyl vinyl ether. The picture shows the crystal structure of [(dme)3CaPh]+ (Ca brown, C gray, O red).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>